Impact of molecular structure and composition of polycarboxylate comb polymers on the flow properties of alkali-activated slag. (February 2019) - Conte, T.; Plank, J.
Abstract: This study is giving new insights on the behavior of polycarboxylate ether (PCE) polymers in alkali-activated slag (AAS). Two systems have been considered: sodium hydroxide (NaOH) and sodium carbonate (Na2 CO3 ) activated slag. A broad range of MPEG (methacrylate), APEG (allyl ether) and IPEG (isoprenol ether) based PCEs exhibiting different molecular structures have been synthesized and tested. First, solubility of the PCE polymers was measured in both alkaline systems. The influence of PCE molecular parameters (side chain length, charge density, chemical composition) was elucidated. Furthermore, impact of the PCEs on the paste rheology was probed via mini-slump experiments. It was found that sufficient solubility of the PCE polymer presents the key property to achieve fluidity. In the NaOH activated system, an allylether maleic anhydride-based PCE possessing short side chain and high solubility produced excellent dispersion. Unfortunately, no PCE polymers which were soluble and efficient in the Na2 CO3 activated system were found.